Information literacy in Web 2.0 environments: emerging dimensions of research (Libellarium: journal for research in the field of information and related sciences, 2015)
Although the conceptual core of information literacy (IL), with its emphasis on acquiring abilities that enable one to ethically seek, use and create information, has remained quite stable since the term was first introduced, recent transformations in experiences of information and information use are subverting the current discourse of IL. Information literacy, in its central features, has always been influenced and determined by information environments. Therefore, it comes as no surprise that in parallel with the advent of Web 2.0, which had transformed information environments into complex and unstructured places, central conceptions of IL are being re-examined and reshaped respectively. IL today, more than ever, should deal less with finding information and focus on evaluating and using or communicating information. In the paper, the author will re-examine the IL concept with regard to developments triggered by the Web 2.0 environment, share her thoughts on the concept “Information Literacy 2.0” and define research challenges and directions initiated by shifts in the IL domain.
Keywords: information literacy; web 2.0; social media; research themes